Examining the nutritional habits of individuals with moderate and severe covid-19, evaluation of changing nutritional habits and physical activity behavior after covid-19 - ÇAĞLAYAN, NİLAY and Nacar, Erkay (Scientific Reports in Medicine, 2025)
Objective: This research aimed to examine the eating habits of adult individuals infected with severe and moderate COVID-19 disease and to evaluate the changing eating habits and physical activity behaviors of post-COVID-19 individuals. Methods: The cross-sectional study included 1340 people over the age of 18 and had a positive PCR test. The data was collected online with the ”Google Form". The obtained data were analyzed with the statistical package program SPSS 25 (Statistical Package for Social Science). Data Mean±Standard Deviation and percentage distribution and the Chi-square test were used in its analysis. p<0.05 significance level was considered statistically significant. Results: It was found that the food consumption of 66.7% of the participants and the number of meals of 82.2% did not change after infection. It has been concluded that individuals do not pay attention to healthy nutrition after infection.It was found that 71.1% of the individuals didn’t do regular physical activity and this situation didn’t change after COVID-19. Conclusion: In line with the results obtained from the study, it is necessary to pay attention to the nutritional habits and physical activity status of individuals. Nutrition education should be provided by dietitians, accurate information should be provided by physical therapists to increase physical activity.